Pengaruh Fitur-Fitur Instagram Terhadap Pemasaran Produk Hijab - Rizky Maulana (Jurnal Transformasi Bisnis Digital, 2024)
This research was created with the aim of finding out the influence of Instagram features on the marketing of Hijab products on the Instagram social media platform. The aim of this research is to find out how much influence Instagram features have on the marketing activities of the hijab.id shop on Instagram social media. The research method used is descriptive qualitative, with data collection techniques through observation and literature study. The research results show that the use of Instagram features as a form of marketing for Hijab.id is utilized as well as possible, so that the level of marketing through Hijabid increases, and the effectiveness of using Instagram features is categorized as very effective, these features are through stories, reels, feeds, direct messages and Instagram shop can make it easier for customers to find out product information and increase attractiveness, while for Supp.id it can increase sales levels